مدى توافر خصائص سلسلة التجهيز الفعّالة في معمل الألبسة الولادية في الموصل: دراسة استطلاعية - غانم محمود أحمد الكيكي (PROSPECTIVE RESEARCHES, 2023)
The Current research is an attempt to identify the extend of availability of agile supply chain characteristics in the Factory of Children Clothes in Mosul. The research problem identified by raising the following questions: 1. To what extent the managers in searched factory have knowledge about the concept of agile supply chain and its characteristics? 2. Does the agile supply chain characteristics available in the searched factory? 3. Are there any differences in managers response in the searched factory for agile supply chain characteristics? To achieve the objectives of research, the current research formulated two hypothesis which has been tested by a set of statistical methods, researcher depend on questionnaire as a main tool to collect data and (32) questionnaires distributed in the research sample, (30) of them has retrieve. The research reached to many conclusions the most important of them: The agile supply chain characteristics are available in the searched factory environment, accordance to the many respondents point of views. An according to findings, the researcher introducing many suggestions that can be beneficial for searched factory.